2007
DOI: 10.1080/00015458.2007.11680081
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Blood Loss with Tranexamic Acid in Primary Total Hip Replacement Surgery

Abstract: Tranexamic acid 15 mg/kg given as a single preoperative bolus dose reduces postoperative and total blood loss, and packed cell transfusion requirements in primary total hip replacement surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
85
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 19 publications
2
85
0
4
Order By: Relevance
“…10,12 The fibrinolytic response after surgery is biphasic. 4,13 The initial phase of increased fibrinolytic activity lasts one hour and is followed by fibrinolytic shutdown, which peaks again after about 24 hours. This is a consequence of increased release of plasminogen activator inhibitor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,12 The fibrinolytic response after surgery is biphasic. 4,13 The initial phase of increased fibrinolytic activity lasts one hour and is followed by fibrinolytic shutdown, which peaks again after about 24 hours. This is a consequence of increased release of plasminogen activator inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…1 The effects of TA on intra-and post-operative blood loss in patients undergoing cemented or uncemented THA have been reported. [1][2][3][4][5][6][7][8][9] We assessed the effects of a single dose of intravenous TA in patients undergoing THA on intra-operative blood loss, postoperative reduction in haemoglobin and haematocrit levels, blood transfusion, incidence of deep vein thrombosis, and the length of hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…So far, a large number of methods for controlling bleeding transfusions were successfully used following TKA, which included autologous blood transfusion, intraoperative blood saving and hypotensive anesthesia [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce this risk, multiple studies have focused on techniques to reduce blood loss in primary THA, with varying results [4,17,[20][21][22][23][24][25][26][27][28][29]. In a meta-analysis conducted by Rosenchner et al [30], the mean expected blood loss in primary THA was found to be 1944 mL.…”
Section: Discussionmentioning
confidence: 98%